2012
DOI: 10.1055/s-0032-1317157
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of β-Fluoro Amides Using Partially Hydrated Nickel Difluoride as Fluorine Source

Abstract: β-Fluoro amides were obtained from the reactions of activated aziridines with partially hydrated nickel difluoride (NiF 2 nH 2 O, n <4) in good yields (47-82%) in the presence of tetran-butylammonium fluoride (20 mol%), while the non-activated aziridines did not react under the same conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Zhang and co-workers reported the ring-opening fluorination of aziridines using an excess of NiF 2 •nH 2 O (2 equiv) as the source of fluorine (Scheme 244). 338 Good yields were obtained when aziridines bore electron-withdrawing groups on the nitrogen atom. The anti isomers were formed exclusively for both regioisomers 77 and 78.…”
Section: Synthetic Methods For the Monofluorination Of Organic Compoundsmentioning
confidence: 99%
“…Zhang and co-workers reported the ring-opening fluorination of aziridines using an excess of NiF 2 •nH 2 O (2 equiv) as the source of fluorine (Scheme 244). 338 Good yields were obtained when aziridines bore electron-withdrawing groups on the nitrogen atom. The anti isomers were formed exclusively for both regioisomers 77 and 78.…”
Section: Synthetic Methods For the Monofluorination Of Organic Compoundsmentioning
confidence: 99%
“…Partially dried NiF 2 (NiF 2 /nH 2 O) produced the best results and the presence of TBAF was crucial to achieve successful transformations. The method worked well with other N ‐activated aziridines too, although monosubstituted aziridines tended to form product mixtures (Scheme ) …”
Section: Fluoride Ring Opening Of Aziridinesmentioning
confidence: 98%
“…The synthesis of β-fluoroamines via ring-opening of aziridines with HF is, in principle, an ideal preparation method because of the low cost of reagents, mild reaction conditions and general accessibility of substrates, but the production of regioisomers and stereoisomers has muddled the efficiency of this strategy. [25][26][27][28] Recently, we reported that DMPU-HF achieved regio-and stereo-control in the fluorination of aziridines. 29 However, the reaction introduces DMPU, which complicates the purification step.…”
Section: Resultsmentioning
confidence: 99%